The Effect of Financial Distress, Foreign Ownership, and Complexity of Company Operations on The Timeliness of Financial Reporting (Empirical Study on Property and Real Estate Sector Companies Listed on The Indonesia Stock Exchange in 2019-2023) - AGUSTIN, Febri Diany; HAPSARI, Dini Wahjoe (Journal of Tourism Economics and Policy, 2024)
The purpose of this study is to determine the impact of management complexity, foreign ownership and financial difficulties on the timeliness of financial reporting for real estate companies listed on the Indonesia Stock Exchange (BEI ) from 2019 to 2023. This study uses secondary data. The financial reports and annual reports are available on the official website of IDX. After using the outlier test to reduce the sample size to 22 companies with 110 observation data, the sampling procedure which involved purposive sampling resulted in 41 companies with 205 observation data. The reliability of financial reporting is not affected by financial difficulties; on the contrary, data analysis using a panel data regression approach and Eviews 12 software shows that foreign ownership and complex business operations have a negative impact on the timeliness of financial reporting. This research provides empirical insights into the factors affecting financial reporting timeliness in Indonesia and the managerial implications in developing programs to improve financial reporting timeliness.